Predictors of mothers’ preventive behaviors for children’s dental trauma: a cross-sectional study using the health belief model - Esmaeil Fakharian; Mojtaba Sehat; Azam Jahangirimehr; Hossein Akbari; KHadijeh Kalanfarmanfarma; Soudabeh Yarmohammadi (BDJ Open)
Abstract Objective Dental traumas are one of the most common reasons for children to visit the dentist. This study aimed to investigate the predictors of mothers’ behavior based on the health belief model (HBM) for the prevention of dental trauma in 7–12-year-old children. Methods The current cross-sectional study was conducted on 700 mothers in Kashan city in 19 September 2023 to 2 March 2024 included in the study by multi-stage random cluster sampling method. The data collection tool was a valid and reliable researcher-made questionnaire consisting of demographic information, Knowledge, constructs of HBM, and preventive behavior for dental trauma. Data were analyzed using SPSS 21 and descriptive statistics (standard deviation, mean, median and range), inferential tests (Pearson correlation coefficient, regression) and path analysis to test the direct and indirect effect of model constructs on the dependent variable by AMOS software. Results Knowledge (r = 0.365, P < 0.001), perceived benefits (r = 0.166, P < 0.001), and self-efficacy (r = 0.425, P < 0.001) had a positive correlation and perceived barriers (r = −0.313, P < 0.001) had a negative correlation and a significant relationship with mothers’ preventive behaviors. Knowledge, perceived barriers and self-efficacy explained and predicted a total of 33% of preventive behavior changes (R-Square=0.329). In the path analysis, self-efficacy (β = 0.327, P < 0.001), knowledge (β = 0.251, P < 0.001) and perceived barriers (β = −0.242, P < 0.001) had the most direct effect, and perceived severity (β = −0.017), perceived susceptibility (β = −0.004), and perceived benefits (β = 0.092) had an indirect effect on mothers’ preventive behaviors (P < 0.05). Conclusion Knowledge, self-efficacy, and perceived barriers were key predictors of mothers’ preventive behaviors. Interventions should target these factors to improve dental trauma prevention in children. The HBM effectively identified these predictors.